Dissociable effects of perceived control on reward-related neural dynamics under risk and ambiguity - Shiting Chen; Menglin Wu; Jianbiao Zhao; Guanglong Liu; Wendeng Yang; Ya Zheng (NeuroImage)
Perceived control plays a crucial role in risk-taking behavior, but its neural effect on reward dynamics in risky and ambiguous decision making remains unclear. Here, we addressed this issue by measuring participants’ (N = 40) EEG activity while they were performing a wheel-of-fortune task. Participants either made choices themselves (a high control condition) or followed the computer's choice (a low control condition) under risky or ambiguous decision contexts. Behavioral and rating data showed a stronger control effect in the risky compared to the ambiguous decision context. In parallel, we found an effect of perceived control on choice evaluation (indexed by the cue-P3) in the risky but not ambiguous context. However, the control effect was more pronounced during feedback anticipation (indexed by the stimulus-preceding negativity) and outcome appraisal (indexed by delta oscillation) in the ambiguous context compared to the risky context. Together, our findings suggest that experiencing control alters reward dynamics in uncertain decision making, with dissociable effects between risk and ambiguity.